Analyzing Social Studies National Curriculum and Textbooks for the Concept of Global Citizenship: A Content Analysis (Journal of Education and Educational Development, 2022)
This research study was an attempt to analyze National Social Studies curriculum and textbooks for Grades IV-V in the context of Global Citizenship to determine if dimensions of global citizenship have been integrated in the curriculum after reviewing the 7th objective of National Education Policy of Pakistan (2009), which shows emphasis on developing individuals who are critical thinkers, intellectual, independent, and most importantly not only responsible citizens in the local context, but as well as responsible towards the globe. Student learning outcomes, teaching and learning process, assessment and evaluation process within the scope of 8 global citizenship dimensions given in the UNICEF global citizenship framework (2013) were examined with Relational content analysis within qualitative paradigm as the research design. Data was collected with the help of a checklist and analyzed with the help of thematic analysis. Some major findings of the research include the emphasis on knowledge and understanding of ‘Economic and political processes’ and ‘World Geography’ in the content areas analyzed. Whereas, the dimension ‘Environment and sustainable development’ and ‘Globalization and interdependence’ is not much reflected in the analyzed content areas.